Influence of entrepreneurship training programmes on unemployed young adults of Ibadan metropolis in Oyo state, Nigeria (2021)
The study examined the influence of entrepreneurship training programmes on unemployed young adults in Ibadan metropolis of Oyo State, Nigeria. Exploratory research design was employed while probability and non-probability sampling techniques were engaged to sample two-hundred and thirty (230) respondents from three main local governments within Ibadan metropolis. Both quantitative and qualitative instrument were used to elicit information. Descriptive and inferential statistical tools were used, while thematic analysis was used to report the qualitative part of the instrument. The empirical findings revealed that young adults’ involvement in entrepreneurship training enhanced them to create employment opportunity for their counterparts; improve their income level; and compete favourably with counterparts in the same line of business among others. Also, it was revealed that challenges facing them are multi-dimensional in nature including; financial constraints, sustaining and upgrading entrepreneurial activities; lack of defined market and weak marketing strategies of the potential and existing young adults involve in entrepreneurs; absence of tax incentives like tax holiday as well as multiple taxation among others. While registration and license fees for potential entrepreneurs; introduction of import substitution strategy to promote indigenous entrepreneurs; provision of reliable infrastructural facilities such as accessible road, and regular powerful supply to ensure effective operation of the needed entrepreneurs and creation of reliable data bank on existing entrepreneurs to mention a few are some of the strategies to overcome these challenges. Recommendations comprised provision of interest free loans, regular implementation ofentrepreneurship trainingprogrammesfor potential young adults and provision of welfare enhancing infrastructural facilities.